TRADISI MBOLO WEKI UNTUK MENGUATKAN NILAI SOLIDARITAS SOSIAL MASYARAKAT TANSMIGRAN SUKU MBOJO DI PLAMPANG KABUPATEN SUMBAWA - anwar anwar; aswar tahir (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2024)
This research is a socio-cultural research with a qualitative descriptive approach which aims to find out about strengthening the value of solidarity, social relations of the Mbojo Tribe transmigrant community in the Mbolo Weki Tradition in SP Perode Village, Plampang District. This research method is to use an interview approach to understand the attitudes, views, feelings and behavior of individuals and groups of people as well as observation and documentation. Informants in this research include village government figures and transmigration community figures who live in Perode Village. Thus, the results of the research show that the people in SP Parode Village, Plampang District have a variety of communities, including the Bima, Lombok, Samawa and Tribal tribes, and each tribe has different cultural patterns